Creating Religious Tolerance through Quran-Based Learning Model for Religious Education - Munawar Rahmat; Endis Firdaus; M. Wildan Yahya (Jurnal Pendidikan Islam, 2019)
Religious tolerance is one of the competencies listed in Indonesia higher education curriculum. There is a need to design learning model that can increase students’ religious tolerance in higher education. This study aims to produce a learning model for religious education which is based on the Quran to nurture students’ religious tolerance. To answer the problem of this study, a quasi-R&D model was chosen. This research is multi-years. In the first year (2019) a learning model was tested. The research findings showed that the lecture model was carried out in six stages: describing the Qur'anic view of the faith of adherents of non-Islamic religions; reminding students of the dangers of takfir; describing students’ common mistakes in assessing other religions; describing the main teachings of other religions correctly; searching for common denominator between Islam and other religions; and developing inclusive attitudes and religious tolerance. After being tested, this learning model has proven to be effective in increasing students' understanding of the basic teachings of other religions, in understanding of the basic teachings of Islam, in developing more robust understanding in their Islamic aqeedah, and being more inclusive and tolerant to adherents of other religions.